Old women in the Odyssey - Jensen, Minna Skafte (Nordlit, 2014)
Being a heroic epic, the Odyssey is peopled by male protagonists in their prime. Nevertheless, the poem gives attention also to humbler figures, among them old women. They are few, but important. A couple of them belong to the highest stratum of society, the rest are slaves. Especially, they are trophoi, nurses, and the impression given is that such nurses are an indispensable part of any big household. The most impressive of them is Odysseus’ nurse Eurycleia, who has a role to play all the way through the poem. When her story is traced from beginning to end it unfolds as a poem inside the poem, with its own inner coherence. Her character is ambiguous: in some scenes she is the quintessence of care and kindness, in others she is brutal, so much so as to make of her one of the scariest characters in the poem. What has made her so full of hatred? the hard life as a slave. She has accustomed herself to her fate and shows unbroken solidarity with her masters, only to feel all the more offended by the amount of work the feasting suitors have caused. Besides, a traditional fairy tale pattern runs as an undercurrent through the epic, with Penelope and Eurycleia filling in the same tale role so that good and bad is split between them.